Rediscovery of Pedicularis denudata (Orobanchaceae), a little known, rare herb after 135 years from India - Borah, Dipankar; Singh, Rajeev Kumar; Garg, Arti (Phytotaxa, 2020)
The hemi-parasitic genus Pedicularis Linnaeus (1753: 607) contains about 671 species, distributed mainly in temperate to tropical mountains and subarctic area of the world, and is the largest genus of the family Orobanchaceae (POWO 2020, Borah et al. 2020, Garg et al. 2020). Presently, 86 species, 13 subspecies and 9 varieties are known from India, of which 20 species, 5 subspecies and 5 varieties are endemic (Husain et al. 2010, Garg & Singh 2015, Singh et al. 2016, Borah et al. 2020, Garg & Singh 2020, Garg et al. 2020). The Himalayan region hosts 83 species, 13 subspecies and 9 varieties, while 2 species Pedicularis perrottetii Bentham (1846: 565) and P. zeylanica Bentham (1835: 54) are confined to the southern Western Ghats.